Design, Synthesis, and Characterization of Lightweight Medium/High Entropy Alloys—A Review - Fainah Madewu; Nicholus Malatji; Mxolisi Brendon Shongwe; Tawanda Marazani; Lehlogonolo Rudolf Kanyane (Engineering Reports)
ABSTRACT Lightweight medium/high‐entropy alloys (MEAs/HEAs) are an emerging class of materials with exceptional properties, including low density, high strength, and enhanced thermal stability. This review explores their design, synthesis, and characterization, emphasizing their potential for high‐performance applications in aerospace and automotive industries. HEAs, typically composed of five or more principal elements in near‐equimolar ratios, form stable solid solution phases due to high configurational entropy, preventing the formation of complex intermetallic compounds. To achieve lightweight yet strong alloys, elements like Al, Mg, Li, and Ti are carefully selected. Computational tools and thermodynamic models play a crucial role in predicting phase stability and optimizing compositions. Various fabrication techniques are employed, including solid‐state processing methods such as mechanical alloying and spark plasma sintering, as well as liquid processing routes such as vacuum induction melting and arc melting with electromagnetic stirring. Advanced additive manufacturing techniques like direct laser fabrication (DLF) and selective laser sintering (SLM) are also effective in producing these alloys. Characterization studies confirm the superior mechanical and thermal properties of HEAs, allowing them to maintain strength and stability even at high temperatures. While these alloys show great promise as replacements for conventional materials, further research and development are needed to fully exploit their potential.